Bar pattern and sediment sorting in a channel contraction/expansion area: Application to the Loire River at Bréhémont (France). (June 2020) - Cordier, Florian; Tassi, Pablo; Claude, Nicolas; Crosato, Alessandra; Rodrigues, Stéphane; Pham Van Bang, Damien
Abstract : Low and high bar modes originate from water discharge variations. In turn, this induces complex compound bar formation. Sediment sorting patterns differ between unit and compound bar patterns. Sediment sorting does not modify bar morphodynamics if sediment mobility is high. Floods decrease the degree of sediment sorting. Abstract: Bars are large sediment deposits alternating with deeper areas that arise from alluvial river bed instability and forcing. The present study aimed at investigating the combined influence of flow and longitudinal width variations on the co-evolution between bar pattern and sediment sorting in a sandy-gravel river reach. To this goal, a fully non-linear 2D numerical model was developed to reproduce the morphodynamic behavior of bars in a reach of the Loire River consisting in a typical channel expansion/contraction. Numerical results showed that varying water discharge promoted a competition between low and high bar modes: i.e., from alternate to multiple bar patterns. Low bar modes were associated with coarse sediment over bar tops and fine sediment in pools, and this sorting pattern was inverted for higher bar modes. Surface sediment was coarser and the degree of sediment sorting was greater after periods of low than high flow. Due to high sediment mobility, sediment sorting did not significantly modify bar morphodynamics.